The cell wall polymer lipoteichoic acid becomes non-essential in Staphylococcus aureus cells lacking the ClpX chaperone - Baek,K; Bowman,L; Millership,C; Dupont,Sogaard M; Kaever,V; Savijoki,K; Varmanen,P; Nyman,T; Grundling,A; Frees,D (mBio, 2016)
Lipoteichoic acid is an essential component of the Staphylococcus aureus cell envelope and an attractive target for the development of vaccines and antimicrobials directed against antibiotic-resistant Gram-positive bacteria such as methicillin-resistant S. aureus and vancomycin-resistant enterococci. In this study, we showed that the lipoteichoic acid polymer is essential for growth of S. aureus only as long as the ClpX chaperone is present in the cell. Our results indicate that lipoteichoic acid and ClpX play opposite roles in a pathway that controls two key cell division processes in S. aureus, namely, septum formation and autolytic activity. The discovery of a novel functional connection in the genetic network that controls cell division in S. aureus may expand the repertoire of possible strategies to identify compounds or compound combinations that kill antibiotic-resistant S. aureus.